157 FAMILIAL HISTORY OF HYPERCHOLESTEROLEMIA AND ALTERED LIPID PANEL IN OVERWEIGHT CHILDREN AND ADOLESCENTS. (1st January 2006) - Kip, K. T.; Evans, W. N.; Mayman, G. A.; Acherman, R. J.; Cass, K. A.; Rothman, A.; Luna, C. F.; Restrepo, H.
Abstract : Background: Serum lipid levels follow familial patterns. Obesity is associated with unfavorable lipid profile and increased cardiovascular risk. Our aim was to assess the relationship of familial history of hypercholesterolemia with the lipid profile in a group of overweight children and adolescents. Methods: This study included 104 children and adolescents, with body mass index (BMI) ≥ 95th percentile, whose parents answered a questionnaire to address the familial history of hypercholesterolemia in first- and second-degree relatives. As part of the program, all participants received nutrition counseling and performed exercise under medical supervision over 12 weeks. Fasting blood samples were drawn at the first visit and at the end of the program. T-test was used for statistical analysis. Results: There were 50 females and 54 males, mean age: 11.3 years (range 7-17 years), mean BMI Z-score: 2.36 ± 0.32, Hispanic: 52%, Caucasian: 30%, African American: 16%, and other races: 2%. At entry there were 44 patients who have one or more relatives with a positive familial history (Group A) and 60 with a negative history (Group B). Comparison in the lipid panel between groups is shown in the table. Conclusions: At entry, the group with a positive familial history showed significantly higher serum levels in the lipid panel than those with a negative history. At the 12th week, initial differences in lipid panel still remained; this could mean that those individuals with a positive familial history require adding to nutrition counseling and medically supervised exercise, another type of intervention to lower their abnormal serum lipid levels.